Experimental and numerical study on seepage-creep coupling characteristics of fault rocks - Gong, Xiaofei; Liu, Yong; Li, Qiang; Ma, Yingjian; Zhai, Minglei; Ma, Dan; Li, Zhenhua; Hou, Jianjun; Qiao, Rui; Li, Jiexiang; Yang, Haiyan; Fan, Limin (Frontiers in Earth Science, 2025)
The fault rocks exhibit low strength, high deformability, and high porosity, making them prone to connecting with the coal seam floor and forming water-conducting channels under the influence of mining activities and aquifer water pressure. Investigating the water inrush mechanism in fault rocks beneath coal seam floors is crucial for ensuring the safety and efficiency of coal mining operations involving fault structures. A test was conducted on the seepage-creep coupling of fault rocks under various stresses, water pressures, and cementation strengths. Based on this, a spatial and temporal evolution model for the seepage-creep coupling characteristics of faulted rocks was developed. The results reveal that the evolution of volumetric strain, flow velocity, porosity, and permeability in the fault rocks can be divided into two stages: the creep compression stage and the expansion damage stage. During the creep compression stage, the samples exhibit more pronounced creep deformation, transitioning into the expansion damage stage earlier under conditions of increased axial pressure, reduced confining pressure, elevated water pressure, and decreased cementation strength. The simulation results align closely with the experimental data. From the creep compression stage to the expansion damage stage, the seepage-creep characteristics evolve gradually at first, followed by a distinct turning point upon entering the expansion stage. This turning point is marked by a rapid increase in volume, along with a sharp rise in flow velocity, porosity, and permeability. Spatially, the seepage-creep characteristics exhibit a non-uniform change from the inlet to the outlet, with expansion damage characteristics first appearing at the outlet. This research provides a theoretical basis for safe and efficient coal mining in fault-affected areas.